Legal Education on Child Protection: Efforts to Reduce the Rate of Dating Violence among Adolescents - Ali, Nuraliah; Farina, Thea; Umar, Mardan (Universitas Pendidikan Ganesha, 2023)
The escalation of violence among vulnerable child groups highlights the pivotal role of knowledge in addressing adversities. This study aims to utilize a Community Service Activity as external educational support to enhance teenagers' comprehension of dating violence and its legal aspects. Legal seminars engaged 88 adolescents from public and private schools in Palangka Raya city. Employing a pretest-posttest design, the intervention proved effective. Results showed a notable 63.63% improvement in adolescents' awareness of legal implications and understanding of potential criminal sanctions. However, marginal progress of 4.5% was observed in refining the definition aspect, indicating a basic understanding of unacceptable behaviors in dating relationships. The success of this initiative is evident in significantly enhancing adolescents' understanding of dating violence and its legal implications. These findings stress the need for tailored educational interventions to strengthen adolescents' legal awareness regarding dating violence. Implications suggest nuanced strategies to fortify understanding of legal protections within relationships, fostering safer environments for vulnerable groups.